Development and characterization of first-in-class PROTAC-based degraders targeting protein N-terminal methylation - Wu, Wei (My University, 2024)
N-terminal methyltransferase 1 (NTMT1) catalyzes the N-terminal methylation of proteins with specific N-terminal sequence motifs, playing critical roles in biological processes including cell mitosis, chromatin interactions, DNA repair, tRNA transport, and genome stability. Dysregulation of NTMT1 has been implicated in many cancers such as malignant melanoma, colorectal, breast, lung, and brain cancers. Notably, NTMT1 is highly overexpressed in colorectal cancer, ranking among the top 1% of proteins that undergo the most significant changes in expression. Moreover, NTMT1 knockout in human colorectal carcinoma (HCT116) cells has shown significant defects in cell proliferation, suggesting that NTMT1 may function as an oncogene and serve as a potential drug target for colorectal cancer, the third most diagnosed cancer and the fourth leading cause of cancer-related deaths globally. While recent efforts have aimed at developing NTMT1 inhibitors, most of which exhibit potent inhibition in vitro but show limited efficacy in cellular models. PROTAC (Proteolysis Targeting Chimera) technology offers a novel approach for targeted protein degradation, with improved potency, selectivity, and extended pharmacodynamic effects. This dissertation explores the use of PROTAC technology to develop NTMT1 degraders with enhanced cellular activity, aiming to elucidate the functional role of overexpressed NTMT1 in colorectal cancer. Consequently, the first-in-class NTMT1 PROTAC, composed of the inhibitor DC541, ethylene glycol linker, and VHL-ligand, was designed, synthesized, and characterized for selective NTMT1 degradation. The NTMT1 PROTAC exhibited high selectivity with degradation occurring in a time- and dose-dependent manner, and NTMT1 expression levels were restored upon PROTAC removal. The degradation of NTMT1 was correlated with antiproliferative effects in colorectal cancer cell lines in both 2D and 3D cultures. Additionally, NTMT1 degradation led to the upregulation of a good prognostic indicator of colorectal cancer, calreticulin (CALR), indicating a possible downstream regulatory mechanism. With the promising results from the first generation of NTMT1 degraders, NTMT1 degrader with higher potency are being designed for improved suitability in cellular studies. To improve the efficiency and accuracy of NTMT1 PROTAC characterization during optimization, a HiBiT-tagged endogenous NTMT1 platform was developed using CRISPR-Cas9-mediated gene knock-in. This platform enabled high-throughput, real-time, continuous monitoring of NTMT1 degradation in live cells, allowing to significantly improve both the efficiency and accuracy of the degrader assessment. Additionally, mass spectrometry-based proximity labeling was developed to explore the NTMT1 protein interaction network. This research highlights the potential of NTMT1-targeted degradation as a strategy for studying protein N-terminal methylation and its role in colorectal cancer.
Keywords: PROTAC; N-terminal methyltransferases 1 (NTMT1); Targeted protein degradation; Proteomics; Proximity labeling; Gene knock-in